Global conservation status of sponges. Issue 1 (February 2015) - Bell, James J.; McGrath, Emily; Biggerstaff, Andrew; Bates, Tracey; Cárdenas, César A.; Bennett, Holly
Abstract Sponges are important for maintaining ecosystem function and integrity of marine and freshwater benthic communities worldwide. Despite this, there has been no assessment of their current global conservation status. We assessed their status, accounting for the distribution of research effort; patterns of temporal variation in sponge populations and assemblages; the number of sponges on threatened species lists; and the impact of environmental pressures. Sponge research effort has been variable; marine sponges in the northeastern Atlantic and Mediterranean and freshwater sponges in Europe and North America have received the most attention. Although sponge abundance has increased in some locations since 1990, these were typically on coral reefs, in response to declines in other benthic organisms, and restricted to a few species. Few data were available on temporal trends in freshwater sponge abundance. Despite over 8500 described sponge species, only 20 are on threatened species lists, and all are marine species from the northeastern Atlantic and Mediterranean. Of the 202 studies identified, the effects of temperature, suspended sediment, substratum loss, and microbial pathogens have been studied the most intensively for marine sponges, although responses appear to be variable. There were 20 studies examining environmental impacts on freshwater sponges, and most of these were on temperature and heavy metal contamination. We found that most sponges do not appear to be threatened globally. However, little information is available for most species and more data are needed on the impacts of anthropogenic‐related pressures. This is a critical information gap in understanding sponge conservation status. Estado Global de la Conservación de Esponjas